1996
DOI: 10.1017/s1355770x00000590
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of deforestation in Mexico

Abstract: This paper uses panel analyses to estimate relationships for agricultural planted area and beef cattle numbers at the state level in Mexico during the period 1970–85, in order to determine the main factors affecting forest land conversion. Of the key policy variables, maize and fertilizer prices appear to be the main influences on the expansion of planted area, whereas beef prices and credit disbursement influence cattle numbers. Population growth also affects both livestock and agricultural activities, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 5 publications
3
88
0
Order By: Relevance
“…Though the effect of population growth rate on land cover dynamics is controversial, elsewhere in many literatures rapid rate of population growth rate one of the root cause for the change of land cover dynamics. According to (Barbier and Burgess 1996), instead of negatively affecting the study concluded that rapid population growth has positive role in availability of resource. On the contrary particularly in the highlands of Ethiopia in which population pressure is intense resulted for resource erosion and degradation (Grepperud 1996).…”
Section: Cause Of Land Use and Land Cover Change Dynamicsmentioning
confidence: 99%
“…Though the effect of population growth rate on land cover dynamics is controversial, elsewhere in many literatures rapid rate of population growth rate one of the root cause for the change of land cover dynamics. According to (Barbier and Burgess 1996), instead of negatively affecting the study concluded that rapid population growth has positive role in availability of resource. On the contrary particularly in the highlands of Ethiopia in which population pressure is intense resulted for resource erosion and degradation (Grepperud 1996).…”
Section: Cause Of Land Use and Land Cover Change Dynamicsmentioning
confidence: 99%
“…Recent conceptual models have attempted to analyse this behaviour (Barbier 1990(Barbier , 1996Barrett 1991 ;Grepperud 1995). The results suggest that several key factors influence the decision of rural households to invest in improved land management.…”
Section: Managing Land Degradationmentioning
confidence: 99%
“…For example, population change elsewhere can foment frontier deforestation through demand for forest and food products (Kaimowitz & Angelsen, 1998;. Worldwide, as many as one-half of all deforestation cases involves demand for food, fuelwood or timber from distant populations to some degree, as documented in several research projects in Latin America, including Costa Rica (Rosero-Bixby & Palloni, 1998) and Mexico (Barbier & Burgess, 1996). Some contemporary LUCC literature has framed the causes of tropical deforestation as underlying and proximate Ojima et al, 1994;Geist & Lambin, 2001).…”
Section: Introductionmentioning
confidence: 99%